Answer:
The value of 9u - 6 is -24
Explanation:
Let us solve the question
∵ -2u + 2 = 6
→ Subtract 2 from both sides to move 2 from the left side to the right side
∵ -2u + 2 - 2 = 6 - 2
∴ -2u = 4
→ Divide both sides by -2 to find the value of u
∵
=
![(4)/(-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1ss8ywlnzsqsjshcu0pny91x98d8f4hgqq.png)
∴ u = -2
∵ The given expression is 9u - 6
→ Substitute u by -2 to find the value of the given expression
∴ 9u - 6 = 9(-2) - 6
∴ 9u - 6 = -18 - 6
∴ 9u - 6 = -24
∴ The value of 9u - 6 is -24